Phase behavior of poly(3‐hexylthiophene‐2, 5‐diyl). Issue 13 (4th March 2016) - Snyder, Chad R.; Gomez, Enrique D.
ABSTRACT: The phase behavior of many conjugated polymers is rich with both crystalline and liquid crystalline phases. Recent computational efforts have identified the isotropic‐to‐nematic transition temperature for polymers such as poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT). Herein, model predictions are combined with experimentally determined values of the equilibrium melting temperature as a function of chain length to provide the complete phase behavior for P3HT. Additionally, because a full description of the phase behavior requires proper accounting for the regioregularity of the chain, a thermodynamic relationship is derived to predict this behavior as a function of both chain length and regioregularity and the impact of regioregularity on the expected phase diagram is discussed. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1202–1206 Abstract : The phase behavior of many conjugated polymers is rich but not yet fully explored. In this work, the crystal‐nematic‐isotropic phase diagram for the semiconducting polymer poly(3‐hexylthiophene‐2, 5‐diyl) is developed as a function of polymer molar mass and regiodefect content. This framework shows the promise of generalization to most semiconducting homopolymers and copolymers exhibiting both liquid crystalline and crystalline phases by combining the tools developed for determining the nematic coupling parameter and the thermodynamic framework discussed in this work.